Ectopic Expression of CDF3 Genes in Tomato Enhances Biomass Production and Yield under Salinity Stress Conditions - Renau-Morata, Begoña; Molina, Rosa V.; Carrillo, Laura; Cebolla-Cornejo, Jaime; Sánchez-Perales, Manuel; Pollmann, Stephan; Domínguez-Figueroa, José; Corrales, Alba R.; Flexas, Jaume; Vicente-Carbajosa, Jesús; Medina, Joaquín; Nebauer, Sergio G. (Frontiers in Plant Science, 2017)
Cycling Dof Factor (CDF) transcription factors (TFs) are involved in multiple processes related to plant growth and development. A member of this family, CDF3, has recently been linked in Arabidopsis to the regulation of primary metabolism and abiotic stress responses, but its role in crop production under stress is still unknown. In this study, we characterized tomato plants overexpressing the CDF3 genes from Arabidopsis and tomato and analyzed their effects on growth and yield under salinity, additionally gaining deeper insights into the molecular function of these TFs. Our results provide evidence for higher biomass production and yield in the 35S::AtCDF3 and 35S::SlCDF3 plants, likely due to a higher photosynthetic capacity resulting in increased sucrose availability. Transcriptome analysis revealed that CDF3 genes regulate a set of genes involved in redox homeostasis, photosynthesis performance and primary metabolism that lead to enhanced biomass production. Consistently, metabolomic profiling revealed that CDF3 evokes changes in the primary metabolism triggering enhanced nitrogen assimilation, and disclosed that the amount of some protective metabolites including sucrose, GABA and asparagine were higher in vegetative tissues of CDF3 overexpressing plants. Altogether these changes improved performance of 35S::AtCDF3 and 35S::SlCDF3 plants under salinity conditions. Moreover, the overexpression of CDF3 genes modified organic acid and sugar content in fruits, improving variables related to flavor perception and fruit quality. Overall, our results associate the CDF3 TF with a role in the control of growth and C/N metabolism, and highlight that overexpression of CDF3 genes can substantially improve plant yield.